Anthropometric Measurements of External Ear of Medical Students in Rupandehi District of Nepal - Pranav Kumar Yadav; Nikita Singh Yadav; Ajay Shah; Nitasha Sharma; Laxmi Bhattarai; Saru Bhattarai; Anjan Palikhey (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Anthropometric refers to the measurements of living human body dimensions for the purpose of understanding human physical variation as it plays major role in prosthetics, plastic surgery. This study aimed to measure the external ear dimensions of medical students in the Rupandehi district, Nepal. MATERIAL AND METHODS This was a cross-sectional study conducted among 100 medical students within October to January 2022 at the Anatomy department of UCMS, Bhairahawa. Samples where MBBS studying students aged 18-21 years enrolled in UCMS. Data were analyzed using SPSS version 22.0. Ear measurements, including total ear length and ear width, were taken using a vernier caliper. RESULTS All parameters, including ear length, ear width, lobular length, and lobular width, were larger in males compared to females and were signiﬁcantly larger on the right side than the left. The difference in ear length (p = 0.00834) and ear width (p = 0.00004) between males and females was statistically signiﬁcant, with males having longer and wider ears on average. CONCLUSION The present study provided the mean values of external ear dimensions of right and left ears of medical students of UCMS, Bhairahawa. These values may provide signiﬁcant information required for supportive evidence in forensic ﬁeld, diagnosis of congenital malformations of ear. Therefore, this information can be used in plastic reconstruction surgeries, designing hearing aids, head phones.